PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Shaka Yudha Pratama; Muhammad Sholahuddin (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This study aims to analyze the effect of service quality and price on customer loyalty, with customer satisfaction as an intervening variable, focusing on muslim fashion consumers in Boyolali. The research method employed is quantitative, utilizing primary data. Data collection was conducted through an online survey method using a questionnaire distributed via Google Forms. The population consists of muslim fashion consumers in Boyolali, with an unknown total population size. Given the large and indeterminate population, the study used the Lemeshow formula, resulting in a sample size of 190 respondents. Purposive sampling was the technique applied for sampling. Data analysis was performed using variance-based structural equation modeling (SEM) Partial Least Square (PLS). The findings indicate that service quality, price, and customer satisfaction all have a positive and significant influence on customer loyalty. Both service quality and price also have a positive and significant influence on customer satisfaction. Furthermore, service quality positively and significantly affects customer loyalty when mediated by customer satisfaction. Similarly, price has a positive and significant effect on customer loyalty when mediated by customer satisfaction. The novelty of this research lies in its focus on the muslim fashion consumer segment in Boyolali, a demographic that has not been extensively studied in this context. This study contributes academically by extending the literature on consumer behavior in the fashion industry and practically by providing insights for fashion retailers in Boyolali to enhance customer loyalty through improved service quality and competitive pricing strategies.